Point-of-Care Genetic Testing Facilitates Rapid Personalization of Antiplatelet Therapy - So, Derek (MD Conference Express, 2011)
The primary objective of the Reassessment of Antiplatelet Therapy using an Individualized Strategy Based on Genetic Evaluation [RAPID GENE; NCT01184300] study was to evaluate the feasibility and test characteristics of a nurse-operated POC genetic test to determine CYP2C19*2 carrier status.